Effect of the Molar Concentration of a Solution on Nanocomposite Crystal Growth in Ferroelectric-Carbon Nanotube Composites Fabricated by using the Sol-gel Method - Kang, Sin Wook; Cho, Sam Yeon; Bu, Sang Don; Han, Jin Kyu (Journal of the Korean Physical Society, 2018)
In this study, Pb(Zr,Ti)O3 (PZT) nanoparticles directly were successfully grown on carbon nanotubes by mixing a PZT solution prepared by using the sol-gel method with functionalized carbon nanotubes. During this process, the effects of the concentration of the PZT solution on the size, crystallinity, and composition ratio of the PZT nanoparticles on the carbon nanotubes were investigated. As the molar concentration of the PZT solution was increased from 0.05 M to 0.2 M, the particle size increased from 6.628 nm to 10.877 nm. As the size of the nanoparticles increased, the surface directions became more diverse. In terms of the crystal structure, the tetragonality of PZT increased with increasing molarity of the PZT solution. This improvement in crystallinity can be further linked to an increase in the ferroelectricity of the PZT-carbon nanotubes, so the nanocomposite fabrication method using carbon nanotubes is expected to affect the characteristics of ferroelectric materials and can be used to further improve the properties of those.